Weed Community Structure Enhances the Persistence of Entomopathogenic Fungi in Peri-Urban Rice Bund Soils - Faza Abdurahman Fiddin; Aminudin Afandhi; Anton Muhibuddin (Jurnal Penelitian Pendidikan IPA, 2025)
The persistence of entomopathogenic fungi (EPF) in agricultural soils is influenced by aboveground vegetation, yet the role of weed community structure remains underexplored. This study evaluated how weed cover, diversity, and abundance affect EPF persistence in bund soils of a peri-urban rice agroecosystem in Mulyoagung, Indonesia. Twenty-five bunds (five replicates per bund type) were sampled using quadrat-based vegetation surveys (125 quadrats total), and composite soil samples were collected for EPF isolation. EPF persistence was assessed using two indicators: (1) colony-forming unit (CFU) counts on selective medium, representing the abundance of fungal propagules regardless of taxonomic identity, and (2) Tenebrio molitor larval bioassays to measure infection potential. Vegetation variables were analyzed using Spearman correlation and Generalized Linear Models (GLMs). Weed cover was significantly associated with higher CFU counts (P = 0.008), and weed diversity was positively correlated with infection rates (P = 0.038); weed abundance showed no significant effect. These findings indicate that complex and diverse weed communities improve microhabitat conditions favorable to EPF survival and pathogenicity. Promoting weed canopy structure and species diversity on bunds may enhance EPF persistence and contribute to sustainable biological control in peri-urban rice farming systems